Corticospinal excitability is associated with hypocapnia but not changes in cerebral blood flow - Hartley, Geoffrey L. (J Physiol, 2016)
KEY POINTS: Reductions in cerebral blood flow (CBF) may be implicated in the development of neuromuscular fatigue; however, the contribution from hypocapnic‐induced reductions (i.e. [Formula: see text]) in CBF versus reductions in CBF per se has yet to be isolated. We assessed neuromuscular function while using indomethacin to selectively reduce CBF without changes in [Formula: see text] and controlled hyperventilation‐induced hypocapnia to reduce both CBF and [Formula: see text]. Increased corticospinal excitability appears to be exclusive to reductions in [Formula: see text] but not reductions in CBF, whereas sub‐optimal voluntary output from the motor cortex is moderately associated with decreased CBF independent of changes in [Formula: see text]. These findings suggest that changes in CBF and [Formula: see text] have distinct roles in modulating neuromuscular function. ABSTRACT: Although reductions in cerebral blood flow (CBF) may be involved in central fatigue, the contribution from hypocapnia‐induced reductions in CBF versus reductions in CBF per se has not been isolated. This study examined whether reduced arterial [Formula: see text] ([Formula: see text]), independent of concomitant reductions in CBF, impairs neuromuscular function. Neuromuscular function, as indicated by motor‐evoked potentials (MEPs), maximal M‐wave (M (max)) and cortical voluntary activation (cVA) of the flexor carpi radialis muscle during isometric wrist flexion, was assessed in ten males (29 ± 10 years) during three separate conditions: (1) cyclooxygenase inhibition using indomethacin (Indomethacin, 1.2 mg kg(−1)) to selectively reduce CBF by 28.8 ± 10.3% (estimated using transcranial Doppler ultrasound) without changes in end‐tidal [Formula: see text] ([Formula: see text]); (2) controlled iso‐oxic hyperventilation‐induced reductions in [Formula: see text] (Hypocapnia), [Formula: see text] ( )= 30.1 ± 4.5 mmHg with related reductions in CBF (21.7 ± 6.3%); and (3) isocapnic hyperventilation (Isocapnia) to examine the potential direct influence of hyperventilation‐mediated activation of respiratory control centres on CBF and changes in neuromuscular function. Change in MEP amplitude (%M (max)) from baseline was greater in Hypocapnia tha in Isocapnia (11.7 ± 9.8%, 95% confidence interval (CI) [2.6, 20.7], P = 0.01) and Indomethacin (13.3 ± 11.3%, 95% CI [2.8, 23.7], P = 0.01) with a large Cohen's effect size (d ≥ 1.17). Although not statistically significant, cVA was reduced with a moderate effect size in Indomethacin (d = 0.7) and Hypocapnia (d = 0.9) compared to Isocapnia. In summary, increased corticospinal excitability – as reflected by larger MEP amplitude – appears to be exclusive to reduced [Formula: see text] , but not reductions in CBF per se. Sub‐optimal voluntary output from the motor cortex is moderately associated with decreased CBF, independent of reduced [Formula: see text].